Service Quality Dimensions and Investor Satisfaction with NEPSE Online Trading System - Karki, Dipendra; Dahal, Rewan Kumar; Bhattarai, Ganesh; Ghimire, Binod (Management Dynamics, 2023)
This study explores the dynamics of service quality and customer satisfaction in the Nepal Stock Exchange (NEPSE) facilitated by online trading services. A total of 400 respondents were surveyed to investigate the factors influencing customer satisfaction in the Nepali capital market. A descriptive research design was employed in the study. The findings suggest that among the factors affecting customer satisfaction, responsiveness, assurance, reliability, and empathy play pivotal roles. Therefore, online trading services in Nepal should prioritize enhancing responsiveness, assurance, reliability, and empathy to increase overall customer satisfaction. This finding has implications for various theoretical frameworks, including the Service Quality Theory. The study also highlights the importance of understanding customer behavior, which is influenced by age, gender, income level, and other variables. It emphasizes the need for online trading service providers to cater to the preferences and behaviors of their diverse customer base, especially the younger generation. Moreover, this research has revealed that improving customer satisfaction can significantly impact the efficacy of online trading services. Service providers should focus on employee training related to customer service, communication, and customer behavior. Additionally, marketers should consider the emotional intelligence of different consumer groups when designing promotional strategies. Recommendations for future research include expanding the study’s geographic scope beyond Kathmandu Valley, increasing the sample size for a more comprehensive analysis, and exploring additional variables.